2022
DOI: 10.3389/fcomp.2021.733531
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement and Pupil Measures: A Review

Abstract: Our subjective visual experiences involve complex interaction between our eyes, our brain, and the surrounding world. It gives us the sense of sight, color, stereopsis, distance, pattern recognition, motor coordination, and more. The increasing ubiquity of gaze-aware technology brings with it the ability to track gaze and pupil measures with varying degrees of fidelity. With this in mind, a review that considers the various gaze measures becomes increasingly relevant, especially considering our ability to make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(58 citation statements)
references
References 269 publications
(363 reference statements)
0
48
0
10
Order By: Relevance
“…Eye tracking glasses are infrared sensors and camera-integrated portable devices that can be easy to wear [ 172 ], as shown in Figure 14 b. This unique platform allows the user to move freely with the head unit’s discretion and freedom for natural head movement [ 160 ].…”
Section: Eye Trackersmentioning
confidence: 99%
“…Eye tracking glasses are infrared sensors and camera-integrated portable devices that can be easy to wear [ 172 ], as shown in Figure 14 b. This unique platform allows the user to move freely with the head unit’s discretion and freedom for natural head movement [ 160 ].…”
Section: Eye Trackersmentioning
confidence: 99%
“…However, some studies indicated the opposite by correlating longer eye fixation with low cognitive stress [95]. Other than eye fixation, rapid eye movement is linked to high visual load and thus associated with higher cognitive load [96]. A high cognitive load state is also linked to more frequent eye blinking [97].…”
Section: A Cognitive Loadmentioning
confidence: 99%
“…Neste método, as áreas destacadas representam uma maior frequência ou probabilidade de localização das fixações. Nesta análise, a ordem das visitas e fixações não é considerada, mas sim a distribuição espacial desses parâmetros (Mahanama et al, 2022). A análise dos mapas de calor é especialmente útil na quando se analisa as regiões da cena visual a que os participantes dedicaram maior atenção (Snider et al, 2021).…”
Section: Movimento Ocularunclassified
“…Fixations refer to the subject's vision focused on a point in space over time. Different fixation characteristics can be measured, such as duration, count, and rate [6,7]. Using these oculomotor parameters, approaches focused on high-order cognitive functions (cognitive demand) have established fixation duration and pupil response as relevant tools for assessing attention, memory, and processing load.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation